2021
DOI: 10.1021/acsomega.1c05713
|View full text |Cite
|
Sign up to set email alerts
|

Bismuth Nanoclusters/Porous Carbon Composite: A Facile Ratiometric Electrochemical Sensing Platform for Pb2+ Detection with High Sensitivity and Selectivity

Abstract: In this work, a ratiometric electrochemical sensor was constructed for the detection of Pb 2+ based on a bismuth nanocluster-anchored porous activated biochar (BiNCs@AB) composite. BiNCs with loose structure and AB with abundant oxygen-containing functional groups are favorable for Pb 2+ adsorption and preconcentration; meanwhile, porous AB provides more mass transfer pathways and increases electronic and ion diffusion coefficients, realizing high sensitivity for P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Summarizing the recent works about metallic nanoparticles/biochar composites, the key effect of biochar is that its porous structure can effectively disperse metallic nanoparticles, and thus make the nano-sized metal provide more activated sites and show enhanced catalytic, redox, or conductive capacities. Therefore, the preparation of metallic nanoparticles (bismuth [ 38 ], mercury [ 39 ], cobalt [ 40 ], and gold [ 11 ]) and biochar nanocomposite yields materials with an excellent analytical and electrochemical performance, combining biochar and metal features in the same device [ 41 ].…”
Section: The Role Of Biochar In the Fabrication Of Electrochemical Se...mentioning
confidence: 99%
See 1 more Smart Citation
“…Summarizing the recent works about metallic nanoparticles/biochar composites, the key effect of biochar is that its porous structure can effectively disperse metallic nanoparticles, and thus make the nano-sized metal provide more activated sites and show enhanced catalytic, redox, or conductive capacities. Therefore, the preparation of metallic nanoparticles (bismuth [ 38 ], mercury [ 39 ], cobalt [ 40 ], and gold [ 11 ]) and biochar nanocomposite yields materials with an excellent analytical and electrochemical performance, combining biochar and metal features in the same device [ 41 ].…”
Section: The Role Of Biochar In the Fabrication Of Electrochemical Se...mentioning
confidence: 99%
“…Another work concerning the detection of Pb 2+ was reported by Zou et al [ 38 ] Considering the low electrical conductivity and easy agglomeration of Bi particles, porous activated biochar (AB) with the merits of high electrical conductivity, large surface area, and good chemical stability was chosen as the support material. In summary, a ratiometric electrochemical platform based on the BiNCs@AB-modified electrode was constructed for the analysis of Pb 2+ in a linear range from 3.0 ng·L −1 to 1.0 mg·L −1 with an LOD of 1.0 ng·L −1 .…”
Section: The Application Of Electrochemical Sensors and Biosensors Ba...mentioning
confidence: 99%
“…Because of their superior self-calibration ability, the development of ratiometric electrochemical sensors has caused the increasing interest to offer the possible application in complicated test conditions. Currently, few metal ions like Bi(III) [16,26] and some redox species as ferrocene (Fc) [27][28][29], thionine (Th) [30], and methylene blue (MB) [31][32][33], are mainly employed as electrochemical signal indicators. Niu et al developed a stable ratiometric electrochemical sensor with the nitrogen doped bimetallic CoNi nanomaterials and MB was used as the internal reference, which realized for detecting p-phenylenediamine in commercial hair dyes [34].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, based on our previous investigation and summarization [ 26 ], we found that porous activated biochar with the merits of good chemical stability and large surface area was appropriately chosen as the support material [ 27 ]. Essentially, the biochar obtained from renewable biomass through pyrolysis or carbonization processes under a low-concentration oxygen atmosphere is porous, eco-friendly, and low-cost [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%